2021
DOI: 10.3389/fnana.2021.767126
|View full text |Cite
|
Sign up to set email alerts
|

Mucin-Type O-Glycosylation in the Drosophila Nervous System

Abstract: Mucin-type O-glycosylation, a predominant type of O-glycosylation, is an evolutionarily conserved posttranslational modification in animals. Mucin-type O-glycans are often found on mucins in the mucous membranes of the digestive tract. These glycan structures are also expressed in other cell types, such as blood cells and nephrocytes, and have crucial physiological functions. Altered expression of mucin-type O-glycans is known to be associated with several human disorders, including Tn syndrome and cancer; how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…To identify high-level functions (i.e., KEGG pathways; , 86, 87) enriched in the 973 gene differentially expressed between facultative and non-cleaner species, we performed pathway analysis using pathfindR (88). 47 KEGG pathways were enriched in our differentially expressed genes including several broadly associated with synaptic function and plasticity, neuronal growth, and neurite elongation such as ribosomal biogenesis (89), ubiquitin-mediated proteolysis (90), extracellular matrix receptors (91), O-glycan biosynthesis (92), and mTOR signaling (93) (Supplementary Table S3).…”
Section: Fig 2b)mentioning
confidence: 99%
“…To identify high-level functions (i.e., KEGG pathways; , 86, 87) enriched in the 973 gene differentially expressed between facultative and non-cleaner species, we performed pathway analysis using pathfindR (88). 47 KEGG pathways were enriched in our differentially expressed genes including several broadly associated with synaptic function and plasticity, neuronal growth, and neurite elongation such as ribosomal biogenesis (89), ubiquitin-mediated proteolysis (90), extracellular matrix receptors (91), O-glycan biosynthesis (92), and mTOR signaling (93) (Supplementary Table S3).…”
Section: Fig 2b)mentioning
confidence: 99%
“…However, little is known about the functions and glycoprotein expression of O-GalNAc glycans in the mammalian brain. Studies in drosophila have shown that O-glycans are essential in brain development, morphology, and synaptic function 35 . However, the bulk of drosophila brain O-glycans are unsialylated Tn antigen and T antigen, which are nearly undetectable in the mammalian brain at baseline 18 .…”
Section: Introductionmentioning
confidence: 99%